Integrative assessment of in situ combined bioremediation strategies applied to remediate soils spilled with sewage sludges - Pérez-Vázquez, A.; Urionabarrenetxea, E.; Artetxe, U.; Rutkoski, C. F.; Gomez-Sagasti, M. T.; Garcia-Velasco, N.; Zaldibar, B.; Anza, M.; Epelde, L.; Garbisu, C.; Becerril, J. M.; Soto, M. (Frontiers in Environmental Science, 2024)
Landfills and waste disposal sites in the Basque Country are summarized in the inventory of soils that either currently support or have supported potentially polluting activities or facilities (Law 4/2015). Notably, "Landfill 17", located in Gernika-Lumo, has been receiving, for decades, sewage sludges from the local wastewater treatment plant (WWTP) as agricultural amendment. In order to decontaminate and recover soil functionality, a combination of bioremediation (involving bioagumentation, phyto-and vermi-technologies) and complementary (i.e. promotion and maintenance of the native vegetation) were implemented in situ. Physico-chemical and ecotoxicological characterization were achieved. Furthermore, an ecotoxicological assessment of the soils upon flora and fauna was carried out through the application of different bioassays and biomarkers. Additionally, an Integrative Biomarker Response Index (IBR/n) was calculated to provide a holistic view of the soil general status.Critical pollutants (Cd, Cr, Ni, Pb, B(a)pyrene and Dieldrin) were observed in most of the treated sites. Microbial parameters did not present remarkable differences among sites.However, plant indicators pointed the non-treated site (MN8) as the unhealthiest. This was also observed in earthworm's immune system where cytotoxicity appeared when exposed to nontreated soils. In conclusion, this field-study showed that the combination of bioaugmentation, phytoremediation with native species and vermiremediation is a highly useful to eliminate mixed contamination and improving soil health and ultimately restoring ecosystem functionality and biodiversity.